Corticosteroids in the management of lymphocytic hypophysitis: Case series - Panigrahi, Manas; Kumari, Manoranjitha; Vooturi, Sudhindra (Neurology India, 2018)
Background: The diagnosis of lymphocytic hypophysitis (LYH) is a clinical challenge. Medical management with steroids may result in complete resolution of the symptoms and radiological features. We report our approach to the diagnosis and treatment of LYH. Materials and Methods: Retrospective analysis of data of nine consecutive patients of LYH from August 2013 to August 2015 was done. The average age of the study population was 38.4 ± 19.8 years, with five (55.5%) women. Presumptive diagnosis of LYH was made in six patients who were treated with steroids. Among the medical intervention group, one patient developed progressive ocular symptoms involving the third cranial nerve, which required surgical intervention. Out of the five remaining patients under medical treatment, four patients showed improvement in clinical symptoms and resolution of radiological features and one patient showed recurrence of the lesion. In the surgical group, the diagnosis was made after the histopathological confirmation. Results: In the surgical group, the diagnosis was made after the histopathological confirmation in all patients except one. All the patients in this group presented with optic nerve compression requiring surgical decompression. All the patients in this group showed symptomatic improvement postoperatively. Symptoms for deficiency of hormones required supplementation dose of steroids. Conclusion: Steroids should be considered as the first line of management in LYH. Surgical resection should be considered in the presence of optic nerve and/or chiasmal compression and for lesions nonresponsive to medical management.